High sCD36 plasma level is associated with steatosis and its severity in patients with genotype 1 chronic hepatitis C. Issue 3 (9th July 2012) - Petta, S.; Handberg, A.; Marchesini, G.; Cammà, C.; Di Marco, V.; Cabibi, D.; Macaluso, F. S.; Craxì, A.
<x xml:space="preserve">Abstract</x> Summary. Soluble CD36 (sCD36) plasma levels, a known marker of cardiometabolic disorders, are associated with surrogate markers of steatosis, while experimental and human studies show a link between CD36 expression in the liver and steatosis. In a cohort of patients with genotype 1 chronic hepatitis C (G1 CHC), we tested the association of sCD36 plasma levels with host and viral factors and sustained virological response (SVR). One hundred and seventy‐five consecutive biopsy‐proven patients were studied. sCD36 plasma levels were assessed by an in‐house ELISA. All biopsies were scored by one pathologist for staging and grading (Scheuer) and graded for steatosis, which was considered moderate–severe if ≥20%. Patients underwent standard of care therapy with pegylated interferon and ribavirin. The severity of steatosis progressively increased according to sCD36 quartiles (P = 0.02); total and low‐density lipoprotein (LDL) cholesterol levels were significantly higher in patients in the lower quartile compared to all the others. Gamma‐glutamyl transferase (P = 0.02), homoeostasis model assessment (HOMA) score (P = 0.002) and sCD36 (P = 0.04) were independently associated with the severity of steatosis as continuous variable. Multivariate logistic regression analysis showed that HOMA (OR 1.243, 95% CI 1.04–1.484, P = 0.01) and sCD36 (OR 1.445, 95%CI 1.135–1.839, P = 0.003) were independently linked to steatosis ≥20%. No association was found between sCD36 and SVR. CD36 is linked to steatosis and insulin resistance in patients with G1 CHC, but does not predict response to treatment. The potential of sCD36 as a surrogate marker of steatosis should be further investigated.